"Etude et amélioration le rendement d'un système photovoltaïque autonome a triplé jonction." - عبدالله, بكوش; محمد الامين, ستو (University of El-Oued, 2022)
"Multi-junction photovoltaic cells (MJSC) are a current trend in the field of photovoltaic cells and form the backbone of concentrator photovoltaic systems. It is an ideal choice because of its high efficiency and better energy productivity. The purpose of this note is to provide a suitable MJSC mathematical model for simulation in MATLAB. This model studies the cell characterization curves. Two different cell types were tested, a normal single junction solar cell and a triple junction solar cell. The thesis also presents simulation results that demonstrate an increase in yield and efficiency of triple- junction cells compared to single-junction cells." """الخلايا الكهروضوئية متعددة الوصلات (MJSC) هي اتجاه حالي في مجال الخلايا الكهروضوئية و تشكل العمود الفقري للأنظمة الكهروضوئية المكثف. إنه اختيار مثالي بسبب ارتفاعه الكفاءة وإنتاجية أفضل للطاقة. الغرض من هذه المذكرة هو توفير شركة MJSC مناسبة نموذج رياضي للمحاكاة في MATLAB. يدرس هذا النموذج منحنيات توصيف الخلية. تم اختبار نوعين مختلفين من الخلايا ، خلية شمسية عادية أحادية الوصلة وخلية شمسية ثلاثية الوصلات. تقدم الأطروحة أيضًا نتائج المحاكاة التي توضح زيادة في العائد وكفاءة ثلاثية مقارنةً بخلايا الوصلة المفردة ""."
مذكرات ماستر تخصص طاقات متجددة
Keywords: Keywords: multi-junction photovoltaic cells, mono-junction cells, triple-junction cells.; الكلمات المفتاحية: خلايا ضوئية متعددة الوصلات ، خلايا أحادية الوصلات ، خلايا ثلاثية الوصلات.